Safety, tolerability, and pharmacokinetics of the anti-IGF-1R monoclonal antibody figitumumab in patients with refractory adrenocortical carcinoma - Haluska, Paul (2009)
PURPOSE: Insulin-like growth factor 1 receptor signaling through upregulation of the stimulatory ligand IGF-II has been implicated in the pathogenesis of adrenocortical carcinoma. As there is a paucity of effective therapies, this dose expansion cohort of a phase 1 study was undertaken to determine the safety, tolerability, pharmacokinetics, and effects on endocrine markers of figitumumab in patients with adrenocortical carcinoma. METHODS: Figitumumab was administered on day 1 of each 21-day cycle at the maximal feasible dose (20 mg/kg) to a cohort of patients with metastatic, refractory adrenocortical carcinoma. Serum glucose, insulin, and growth hormone were measured pre-study, at cycle 4 and study end. Pharmacokinetic evaluation was performed during cycles 1 and 4. RESULTS: Fourteen patients with adrenocortical carcinoma received 50 cycles of figitumumab at the 20 mg/kg. Treatment- related toxicities were generally mild and included hyperglycemia, nausea, fatigue, and anorexia. Single episodes of grade 4 hyperuricemia, proteinuria, and elevated gamma-glutamyltransferase were observed. Pharmacokinetics of figitumumab was comparable to patients with solid tumors other than adrenocortical carcinoma. Treatment with figitumumab increased serum insulin and growth hormone levels. Eight of 14 patients (57%) had stable disease. CONCLUSIONS: The side effect profile and pharmacokinetics of figitumumab were similar in patients with adrenocortical carcinoma in comparison to patients with other solid tumors. While hyperglycemia was the most common adverse event, no clear patterns predicting severity were observed. The majority of patients receiving protocol therapy with single agent figitumumab experienced stability of disease, warranting further evaluation.